Ecohealth as a field: Looking forward - Saint-Charles, J.; Webb, J.; Sánchez, A.; Mallee, H.; Welden de Joode, B. van; Hung Nguyen-Viet (Springer, 2014)
This forum paper proposes a reflection on the “field of ecohealth” and on how best to sustain a supportive environment that enables the evolution of diverse partnerships and forms of collaboration in the field. It is based on the results of a preconference workshop held in October 2012, in Kunming, China at the fourth biennial conference of the International Association for Ecology and Health. Attended by 105 persons from 38 countries, this workshop aimed to have a large-group and encompassing discussion about ecohealth as an emerging field, touching on subjects such as actors, processes, structures, standards, and resources. Notes taken were used to conduct a qualitative thematic analysis combined with a semantic network analysis. Commonalities highlighted by these discussions draw a portrait of a field in which human health, complex systems thinking, action, and ecosystem health are considered central issues. The need to reach outside of academia to government and the general public was identified as a shared goal. A disconnect between participants’ main concerns and what they perceived as the main concerns of funding agencies emerged as a primary roadblock for the future.